Prinsip Maslahah Dalam Penyelenggaraan Bidang Jaminan Produk Halal - Salman Hikam; Karimatul Khasanah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze Government Regulation Number 39 of 2021 concerning implementing the Halal Product Assurance Sector with the principle of maslahah. With a normative legal research method through a statutory and conceptual approach. The results of the study show that the articles that have drawn criticism are in article 39. Halal Auditors are limited to being registered with only one Halal Inspection Institution. This shows that there is maslahah khassah, namely that Halal Auditors only provide specific benefits for one LPH or it can be said that there is still an element of harm because it still limits the profession of other Halal Auditors. Article 81, regarding free halal certification financing facilities for business actors, the policy of providing free certification facilities for business actors, makes BPJPH have a limited role in the halal certification process, because the halal certification process is required through a halal product companion. Article 150, regarding the imposition of sanctions that violate articles 93 and 94. Business actors who produce non-halal products are required to include a non-halal statement on their products. However, BPJPH is not given full authority to impose heavy administrative sanctions on business actors, which also has the potential to cause harm.